The use of audiovisual stimulation in learning gymnastic elements - Šešum, A.; Kajtna, T. (Science of Gymnastics Journal, 2018)
Nowadays, more and more people are aware of the difficulty to reach imposed goals and in their craving to improve their performance they often turn to different methods that help them realize their goals. The market offers many services, methods, products and machines that guarantee and promise better results. The purpose of this research was to study the impact of audio-visual stimulation (hereinafter: AVS), followed by visualization of gymnastic elements, on the improvement in performance of those gymnastic elements. The study was conducted on 39 first year students of the Faculty of Sport in Ljubljana, which attended the classes of Gymnastics and 19 of them, who were in the experimental group, attended AVS lessons twice a week. We expected AVS and visualization sessions to effect motor learning of gymnastic elements positively. Through the students' execution of gymnastic elements it was established how much the students had improved from the first lesson to the assessment. For audio-visual stimulation, the device "Therapeut", where the participants attended an 11 minute program, that stimulated alpha and beta waves and should leave the participants refreshed and creative. Meters to determine heart rate and blood saturation, music and questionnaires with a scale to determine well-being were used. Progress of motoric learning of gymnastic elements, heart rate decline as well as changes in saturation and well-being were monitored. No results obtained in the observed parameters showed that we had any impact on the improvement and our study did not reveal any impact of AVS on the improvement of the observed parameters.